Ontario’s Family Health Teams: Politics Within the Model - Ashcroft, Rachelle (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2015)
This article provides an overview of political decisions that led up to the implementation of the Ontario Family Health Team (FHT) model. FHTs have broadened primary health care in Ontario by bringing together family physicians with various interdisciplinary professionals. Political decisions have long influenced the shape and need for the FHT model. Knowledge of historically imbedded elements in the FHT model helps to strengthen current and future policy and decision-making. This article is informed by qualitative data collected from interviews with seven policy informants and 29 FHT leaders.